O Nazismo na percepção dos apoiadores de Hitler: um estudo sobre as cartas enviadas aos NSDAP e ao Estado Nazista (1925-1939) - Drumond, Jeanine Poock de Almeida (2017)
This dissertation aimed at analyzing the letters that were sent to Hitler between the years of 1925 and 1939 to understand how power was self-constituted with public opinion. From the letters analyzed, we sought to explain the main events between this period, in view of Hitler's views on his political program (1925-1933) and the Nazi state until the beginning of World War II (1933-1939). Through public opinion we sought to understand the scope of Nazi propaganda and how it influenced voters. The letters analyzed in this research demonstrated a high level of veneration, loyalty and fanaticism by the Nazi leader and from the analyzes we tried to clarify how the process of the seizure took power by the Nazis and how the government of Hitler consolidated in Germany.